High‐Performance Semi‐Transparent Organic Photovoltaic Devices via Improving Absorbing Selectivity. Issue 11 (27th January 2021) - Li, Yaokai; He, Chengliang; Zuo, Lijian; Zhao, Feng; Zhan, Lingling; Li, Xin; Xia, Ruoxi; Yip, Hin‐Lap; Li, Chang‐Zhi; Liu, Xu; Chen, Hongzheng
Abstract: Semi‐transparent organic photovoltaics (ST‐OPVs) are promising solar windows for building integration. Improving the light‐absorbing selectivity, that is, transmitting the visible photons while absorbing the invisible ones, is a key step toward high‐performance ST‐OPV. To achieve this goal, the optical properties of the active layer, transparent electrode, and capping layer are comprehensively tailored, and a highly efficient ST‐OPV with good absorbing selectivity is demonstrated. First, a numerical method is established to quantify the absorbing selectivity of materials and devices, based on which, an infrared absorbing non‐fullerene acceptor, that is, H3, is selected among a large pool of photo‐active materials. Second, an ultra‐smooth transparent thin Ag layer with small granule size is developed via polyethylenimine wetting, which alleviates light scattering and improves the electric properties for ST‐OPV. Finally, as guided by optical simulation, a TeO2 capping layer is deposited on top of the ultra‐thin Ag to further improve the light‐absorbing selectivity. As a result, the light utilization efficiency is significantly improved to 3.95 ± 0.02% (best ≈4.06%), with a good color rendering index of 76.85. These results make it one of the best among color‐neutral ST‐OPVs. This work stresses the importance of manipulating the light‐absorbing selectivity for high‐performance ST‐OPVs. Abstract : High‐performance organic semi‐transparent photovoltaic (ST‐OPV) devices are achieved by improving the light‐absorbing selectivity, that is, the light‐absorbing capability in invisible regions and light transmission in the visible region. Systematic optimization, including developing a numerical method for photo‐active layer screening, interface engineering, and optical manipulation, enables high‐performance ST‐OPVs with the best light utilization efficiency of 4.1%, ranking among the highest for ST‐OPVs.